Identification of three cannabimimetic indazole and pyrazole derivatives, APINACA 2H‐indazole analogue, AMPPPCA, and 5F‐AMPPPCA. Issue 2 (9th March 2016) - Jia, Wei; Meng, Xin; Qian, Zhenhua; Hua, Zhendong; Li, Tao; Liu, Cuimei
Abstract : This paper reports analytical properties of three cannabimimetic indazole and pyrazole derivatives seized from a clandestine laboratory. These three new synthetic cannabinoids include N ‐(1‐adamantyl)‐2‐pentyl‐2 H ‐indazole‐3‐carboxamide (APINACA 2 H ‐indazole analogue, 1 ), N ‐(1‐adamantyl)‐4‐methyl‐1‐pentyl‐5‐phenyl‐1 H ‐pyrazole‐3‐carboxamide (AMPPPCA, 2 ), and N ‐(1‐adamantyl)‐1‐(5‐fluoropentyl)‐4‐methyl‐5‐phenyl‐1 H ‐pyrazole‐3‐carboxamide (5F‐AMPPPCA, 3 ). These compounds were identified by liquid chromatography‐quadrupole time‐of‐flight‐mass spectrometry (LC‐QTOF‐MS), gas chromatography‐time‐of‐flight‐mass spectrometry (GC‐TOF‐MS), and nuclear magnetic resonance (NMR) spectroscopy. No analytical properties and pharmacological activities about compounds1–3 have appeared until now, making this the first report on these compounds. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Three cannabiminetic indazole and pyrazole derivatives, APINACA 2H‐indazole analog, AMPPPCA, and 5F‐AMPPPCA were identified using LC‐QTOF‐MS, GC‐MS, and NMR